2009
DOI: 10.1590/s0004-282x2009000500005
|View full text |Cite
|
Sign up to set email alerts
|

Neurological congenital malformations in a tertiary hospital in south Brazil

Abstract: -Background: Congenital anomalies are one of the main causes of morbidity and mortality among infants. The involvement of the central nervous system (CNS) occurs in 21% of cases. Objective: To identify incidence of CNS malformations and associated factors in newborns at a Terciary Hospital of Porto Alegre. Method: Case-control study conducted between 2000 and 2005 based on the Latin American Collaborative Study of Congenital Malformations database. Results: Among 26,588 births registered in this period, 3.67% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
1
12
0
6
Order By: Relevance
“…With respect to age, many of the mothers were relatively young. This finding corroborates other studies [6], [8] in the literature showing that prevalence of hydrocephalus is higher in children of young mothers.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…With respect to age, many of the mothers were relatively young. This finding corroborates other studies [6], [8] in the literature showing that prevalence of hydrocephalus is higher in children of young mothers.…”
Section: Discussionsupporting
confidence: 92%
“…Other authors have also demonstrated a minimum standard of education in studies of this disease [20]. Brazilian studies showed that 46.1% of mothers of children with congenital malformations had only basic education and educational level ranged from 1 to 11 years of study [8], [21]. The low educational levels observed in this study might be related to the local research institution, which serves the lower social classes of the Brazilian Unified Health System.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…(29) . This NTD prevalence was almost half the 9?60/1000 prevalence reported from Porto Alegre for the time period 2000-2005 (30) . In contrast, NTD prevalence in hospital registry data from Minais Gerais and Sao Paulo for comparable time periods ranged from 1?13 to 4?87 per 1000 live births (16,31) .…”
Section: Regional and Local Prevalence Estimatesmentioning
confidence: 63%